Histologic evaluation of the use of membrane, bone graft, and MTA in apical surgery - Bernabé, Pedro Felício Estrada [UNESP]; Gomes Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Moretto, Marcelo Juliano [UNESP]; Lodi, Carolina Simonetti [UNESP]; Nery, Mauro Juvenal [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Dezan Junior, Eloi [UNESP] (Mosby-elsevier, 2010)
The aim of this study was to evaluate the periapical healing after the use of membrane, bone graft, and mineral trioxide aggregate (MTA) in apical surgery of dogs' teeth. Apical lesions were induced in 48 roots of 6 dogs after coronal access and pulpal removal. Apical surgery consisted of osteotomy with trephine bur for the standardization of the critical surgical cavities, followed by apicoectomy, curettage, preparation of the root-end cavities with the aid of the ultrasonic device, and retrofilling with MTA. The surgical sites were divided into: group 1-filled with blood; group 2-filled with blood and recovered with membrane; group 3-filled with bone graft; and group 4-filled with bone graft and recovered with membrane. The results showed that the inflammatory infiltrate, the periapical healing process, and the behavior of MTA was the same in all groups, including the mineralization stimulation. It was concluded that the use of membranes and bone graft materials isolated or associated in apical surgery did not alter the periapical healing process after the root-end filling with MTA. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010; 109: 309-314)